Victimization and its associations with peer rejection and fear of victimization: Moderating effects of individual-level and classroom-level characteristics - Kollerová, Lenka; Smolík, Filip (British journal of educational psychology, 2016)
BACKGROUND: Past research has shown that peer victimization by bullying is associated with peer rejection and fear of victimization, but little is known about the interplay between victimization and other characteristics in the prediction of these experiences. We assume that the associations between victimization and peer rejection/fear of victimization are moderated by multiple characteristics, including aspects of peer ecology. AIMS: The study tested whether the links between victimization and peer rejection/fear of victimization are moderated by gender, peer support, and two features of classroom peer ecology: classroom victimization rate and classroom hierarchy (the variability of popularity among students). SAMPLE: The sample included 512 early adolescents attending sixth grade retrieved from 25 elementary school classrooms. METHODS: Participants completed a set of self-report and peer nomination instruments in classroom settings. RESULTS: Multilevel linear modelling showed that higher levels of peer rejection were associated with higher victimization, male gender, and lower peer support. The association between victimization and peer rejection was attenuated for females and when the classroom victimization rate was higher. A higher fear of victimization was related to higher victimization, female gender, lower peer support, and a higher classroom victimization rate. The link between victimization and fear of victimization was strengthened by female gender and higher levels of classroom hierarchy. CONCLUSIONS: The results indicate the relevance of the interplay between victimization and gender and between victimization and classroom peer ecology in understanding peer rejection and fear of victimization.
Keywords: Social Support; Female; dítě; šikana; ženské pohlaví; Peer Group; Adolescent; lidé; Bullying; Fear; strach; Sex Factors; vyrovnaná skupina; Rejection, Psychology; Male; sexuální faktory; odmítání (psychologie); Child; mužské pohlaví; Crime Victims; oběti zločinu; mladiství; sociální opora; Humans